E-Lifestyle And Internet Advertising Avoidance - Widarto Rachbini, Iha Haryani Hatta (Jurnal Manajemen, 2018)
E-lifestyle behavior towards avoiding internet advertising needs to be known to design an advertisement on the internet, so that the tendency of avoiding internet advertising can be reduced.Therefore, research on e-lifestyle and internet advertising avoidance is needed which aims to find out the influence of each e-lifestyle on Internet advertising avoidance and the behavior of each e-lifestyle towards Internet advertising avoidance activities. The population of this study is Internet users. A sample of 200 Jakarta residents were selected by purposive sampling technique. Data were analyzed using Structural Equation Modeling (SEM). The results obtained after the data were analyzed show that need-driven, interest-driven, entertainment-driven, sociability-driven, and novelty-driven influence the avoidance of Internet advertising. But Importance-driven and concern-driven e-lifestyle have no influence. In addition, entertainment-driven e-lifestyle has the largest factor loading value on average. This indicates that the majority of respondents are entertainment-driven in using the Internet everyday.